Hikmah as a Method of Da‘wah : Historical Contribution of Women Preachers in the Prophetic Era - Zarin Tasnim; Md. Ruhul Amin (LECTURES: Journal of Islamic and Education Studies, 2026)
Da‘wah represents a fundamental mission of Islam aimed at guiding humanity through ethical communication and intellectual engagement. Among the Qur’anic approaches to da‘wah, hikmah functions as a central methodological principle that emphasizes knowledge, moderation, empathy, and contextual understanding. This article examines hikmah as an effective method of da‘wah and investigates how it was practically embodied through the preaching activities of early Muslim women during the Prophetic era. Employing qualitative method and historical analysis based on Qur’anic teachings, Prophetic traditions, and early Islamic historical sources, the study explores women’s participation in religious instruction, transmission of hadith, moral counselling, social reform, and family-based religious guidance. The findings of the research reveal that early Muslim women were active representative in the dissemination of Islamic teachings and applied wisdom-centred strategies that strengthened communal learning and spiritual development. Their approaches reflected intellectual authority, ethical persuasion, and socially responsive communication, demonstrating that women’s da‘wah contributions were integral to the formation of the early Muslim community.